Investigation of Attitudes and Perceptions of Human Resource Managers at Hospitality Establishments Regarding Affirmative Action Programs A Case Study in Eski?ehir-Turkey - Uysal, Davut; Rahman Temizkan; Nazmi Taslacı (European Journal of Multidisciplinary Studies, 2017)
The purpose of this study is to examine the perceptions and attitudes of human resource managers at some hospitality organisations regarding the employment of disadvantaged individuals as part of affirmative action program in the province of Eski?ehir-Turkey. This study is a qualitative study focusing on real cases to inspire other organisations. The data were collected through active interviews, and the collected data was analysed through the use of manual qualitative data analysis methods. The findings of the study reveal that perceptions of human resource managers regarding disadvantaged individuals at hospitality organisations are closely related to disabled individuals. They do not have positive attitudes towards the employment of disadvantaged individuals in tourism as part of affirmative action programs. They are also against positive discrimination of disadvantaged individuals in the employment in tourism for some reasons. All these findings suggest that participants are confused about some terms regarding affirmative action.